THE EFFECT OF PRINCIPAL SUPERVISION, SCHOOL CULTURE, AND WORK MOTIVATION ON THE PERFORMANCE OF PUBLIC ELEMENTARY SCHOOL TEACHERS - AZIZAH, Azizah; A. GHANI, Abd. Rahman (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2025)
The purpose of this study is to analyze the effect of principal supervision, school culture, and teacher work motivation on teacher performance The method in this study is a causal survey method with path analysis techniques. The population in this study were all elementary school teachers in Cluster 1 of Periuk District, Tangerang City, totaling 139 teachers. With a sample of 103 teachers taken based on proportional random sampling, with path analysis techniques. The findings of this study reveal that principal supervision plays an important role in improving teacher performance. Effective supervision not only provides direction and control but also motivates teachers to carry out their tasks more responsibly and professionally. Likewise, school culture is shown to have a significant positive influence on teacher performance, where a conducive and collaborative culture fosters discipline, responsibility, and innovation among teachers. In addition to its direct impact on performance, principal supervision also has a strong effect on teacher work motivation, while school culture contributes positively to encouraging teachers to remain enthusiastic and committed in fulfilling their duties. Furthermore, teacher work motivation itself significantly enhances teacher performance, indicating that motivated teachers are more likely to achieve optimal results in the learning process. Another important finding is that principal supervision strongly shapes school culture, suggesting that leadership style and supervisory practices influence the values, norms, and habits that develop within the school environment. Collectively, these results highlight the interrelationship between supervision, school culture, and teacher motivation as key determinants of teacher performance improvement.